Analisis Visual Model Wanita Pada Iklan Judi Online - Sheila Laurencia; Salsabila Almanjakani Aminuddin; Hervalaura Rahmanti; Rachel Olivia (Journalism, Public Relation and Media Communication Studies Journal (JPRMEDCOM), 2022)
The rapid development of Science and Technology has made such a rapid change. Human creativity is increasing, making more innovations appear in the field of technology, one of which is the internet. As technology develops, online games were originally just games, now they have been developed into a money-making medium or what is commonly called online gambling. In Indonesia itself, there are still several online gambling advertisements that accidentally appear around the web page being visited. The design itself has an important role in communicating, one of which is in advertisements to promote something to people, designs in advertisements must have characteristics that can leave an impression when seen. According to JB Reswick (in Pilliang, 2008, p. 384) design is a creative activity that involves creating something new and useful that did not exist before. Online gambling advertisement posters that have been widely spread on the internet have similar visual styles to each other, one of the most prominent is the model used, which is a woman in open clothes and oriental skin. Such a visual style can attract the attention (it can also be called clickbait) of many people, especially men, to want to visit these online gambling websites.